2006
DOI: 10.1007/bf03022832
|View full text |Cite
|
Sign up to set email alerts
|

Regional Anesthesia and Pain

Abstract: Purpose: Not all bone cancer pain can be effectively treated with current therapies. In the present study, the effects of ip administration of α-2 agonists (dexmedetomidine and clonidine), N-methyl-D-aspartate (NMDA) antagonists (MK-801 and ketamine), an N-acetylaspartylglutamate peptidase inhibitor (ZJ-43), and morphine were examined in a mouse bone cancer pain model. Methods:A bone cancer pain model was produced by injection of murine sarcoma cells into the medullary cavity of the distal femur. To estimate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Preclinical and clinical research has shown that blocking NMDA receptors produces a significant analgesic effect on bone cancer pain 20, 21, 26, 32 , suggesting that NMDA receptors are required for the induction of bone cancer-evoked pain hypersensitivites. To test whether spinal NMDA receptors are involved in PCC-induced activation of dorsal horn mTOR and its downstream pathway, the rats were infused i.th.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical and clinical research has shown that blocking NMDA receptors produces a significant analgesic effect on bone cancer pain 20, 21, 26, 32 , suggesting that NMDA receptors are required for the induction of bone cancer-evoked pain hypersensitivites. To test whether spinal NMDA receptors are involved in PCC-induced activation of dorsal horn mTOR and its downstream pathway, the rats were infused i.th.…”
Section: Resultsmentioning
confidence: 99%
“…Given that NMDA receptors play a critical role in spinal central sensitization 18, 33 and that blocking NMDA receptors produces a significant analgesic effect on bone cancer pain 20, 21, 26, 32 , we propose that spinal cord NMDA receptor-mediated activation of mTOR and its downstream effectors is required for development and maintenance of bone cancer-induced pain hypersensitivities. We used a rat model of bone cancer pain produced by prostate cancer cell (PCC) injection of the tibia to determine first whether pre- and post-treatment with i.th.…”
Section: Introductionmentioning
confidence: 98%
“…4,1721 Microinjection of a GCPII inhibitor into either the PAG or RVM, important nuclei in the descending pain pathway, produced an analgesic effect in the rat formalin model of inflammatory pain. 22 Similarly, the locus coeruleus (LC) is a key nucleus of the descending pain inhibitory system.…”
Section: Introductionmentioning
confidence: 99%
“…Ketamine produces the partial inhibition of mechanical allodynia of skin cancer at an intraperitoneal dose of 30 mg/kg 13) and the complete inhibition of pain-related behaviors of mice with bone cancer. 19) Thus, the analgesic efficacy of ketamine may also depend on the types of cancer and pain.…”
Section: Discussionmentioning
confidence: 99%